Apple Incorporated : European Commission Fines for Tax Evasion (B) - Edwards, Jordan W. (SAGE Knowledge. Cases., 2017)
The case outlines Tim Cook's reaction to the EU's decision that Apple had received special treatment in terms of its taxation in Ireland and the order to pay 13 billion euros plus interest in tax.